2015
DOI: 10.12669/pjms.315.7683
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wavefront Optimized LASIK on Higher Order Aberrations in Myopic patients

Abstract: Objective:To determine mean change induced in root mean square value of higher order aberrations in myopic patients undergoing wavefront optimized laser assisted in situ keratomileusis.Methods:This quasi experimental study was conducted at Armed Forces Institute of Ophthalmology, Rawalpindi, Pakistan from Jan 2014 to Dec 2014. Sixty eyes of 35 myopic patients were included in the study. All patients underwent wavefront optimized (WFO) laser assisted in situ keratomileusis (LASIK) using femtosecond laser (FM 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Studies show that myopic excimer corneal ablations cause postoperative HOAs [26,[43][44][45], and these increase with greater myopic correction [43,44,46].…”
Section: Complicationsmentioning
confidence: 99%
“…Studies show that myopic excimer corneal ablations cause postoperative HOAs [26,[43][44][45], and these increase with greater myopic correction [43,44,46].…”
Section: Complicationsmentioning
confidence: 99%
“…[27][28][29][30] Several studies have reported that a large part of patients experienced night vision symptoms when they had undergone with laser in situ keratomileusis (LASIK) or CRT. 9,10,15,31 Different authors found increasing higher-order aberrations and reducing low-contrast best-corrected Vision Quality of Life after LASIK and Overnight CL wear 4 visual acuity, [32][33][34][35][36][37][38][39][40] however it should be noted that in many patients the vision-related quality of life shown to be good. 12,15 These seemingly contradictory trends point to the fact that other factors than visual performance have an important role in patient satisfaction after refractive surgery or overnight CL wear.…”
Section: Introductionmentioning
confidence: 99%
“…HOAs can have a great influence on visual quality (15), and hence third order aberrations (S3-S6) and total highorder aberrations (Sh) were measured. Khan et al (16) reported that among Zernike coefficients, coma, spherical and HOAs significantly increased 1.86-, 2.44-, and 1.56-fold, respectively, at 1 month after FS-LASIK, suggesting obvious spherical aberration. Wang et al (10) reported that HOAs on the whole and anterior corneal surfaces increased significantly at 1 month after surgery, and the spherical aberration on the whole corneal and anterior corneal surfaces were significantly increased at 1 and 3 months postoperatively, along with the vertical coma on the whole and anterior corneal surfaces at 1 and 3 months.…”
Section: Discussionmentioning
confidence: 99%